Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Group photo: Robin Watkins and ? with young daughter; standing: ?, Victor McLane, ?, Marcia McLane,?, Louise Erickson, ?, Lindell Cross, ?, Barbara Gaines, ?, Mary Ellen Clay, Linda Mack, ?, and